2016
DOI: 10.1007/s10895-016-1787-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-Fold C 3-Symmetric Off-On Fluorescent Chemo-Sensors for Fluoride

Abstract: Three novel C 3-symmetric tris-salicylaldimine Schiff base based "off-on" fluorescence sensors have been designed and synthesized. The synthetic approach involves a simple imine bond (C = N) formation between 1,3,5-tris(4'-aminophenyl)benzene (TAPB) and 3,5-substituted salicylaldehydes. The presence of salicylaldehyde units on periphery of the tris-salicylaldimine Schiff bases masks the fluorescence of TAPB core. Interestingly, binding of fluoride ions to the salicylaldehyde units turns the fluorescence "on" i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…This triboron complex was found to be a blue‐light emitter. Murugavel and co‐workers also used building block 181 in the synthesis of several tris‐benzaldimine and tris‐salicylaldimine Schiff‐base sensors …”
Section: Carbon−nitrogen Bond‐forming Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This triboron complex was found to be a blue‐light emitter. Murugavel and co‐workers also used building block 181 in the synthesis of several tris‐benzaldimine and tris‐salicylaldimine Schiff‐base sensors …”
Section: Carbon−nitrogen Bond‐forming Reactionsmentioning
confidence: 99%
“…This triboron complex wasf ound to be ab lue-light emitter.M urugavel and co-workersa lso used buildingb lock 181 in the synthesis of severalt ris-benzaldimine and tris-salicylaldimine Schiffbase sensors. [79] Bednaříkovµ et al reported the synthesis of star-shaped amines and studied their interactions with cyclodextrinsa nd permethylated derivatives (Scheme 111). [80] Ap alladium-catalyzed SM cross-coupling reaction between readily accessible 1,3,5-tribromobenzene (75)a nd ester-substituted phenylboron-ic acid (348)i nP EG-400a fforded triesterd erivative 349 (88 % yield).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…[59][60][61][62] It has been shown that uoride binds with the -OH proton of the salicylaldimine Schiff base through hydrogen bonds. 59,[63][64][65][66][67] A sensor molecule that comprises a salicylaldimine receptor connected to a uorophore unit can effectively be used as a uorescence turn-on sensor for uoride. We have synthesized three different Schiff bases, 25-27, from a reaction of 1 with three different salicylaldehydes (Scheme 5).…”
Section: Fluoride Sensingmentioning
confidence: 99%
“…We have synthesized three different Schiff bases, 25–27, from a reaction of 1 with three different salicylaldehydes ( Scheme 5 ). 63 These Schiff bases contain three salicylaldimine groups and a 1,3,5-TPB core to serve as the anion receptor and fluorophore, respectively. Due to the rapid isomerization of –C N– linkages and intramolecular PET, these Schiff bases are very weakly fluorescent in their pristine state.…”
Section: Ion Sensingmentioning
confidence: 99%
See 1 more Smart Citation